Bureaucratic structure of the Transit Commission of Ecuador: weberianity and autonomy - Haoulo Mubayed, Mohammad (2023)
This article analyses the bureaucratic structure of the Ecuadorian Transit Commission (CTE), an institution that oversees transport management and safety, in a Weberian and autonomy-based approach. The study employs structural measurement tools designed by Peter Evans and James Rauch. The assessment of bureaucratic performance, based on career, salary and merit indices, suggests that the CTE has good institutional capacity (8.17/10.0 points). However, its institutional autonomy is low and is an institution that is politically permeable to the intervention of different state actors from the executive and municipal branches. In addition, the Law on Surveillance Corps Personnel (1970) and the focus on old institutional structures affect bureaucratic performance. Finally, civil servants perceive that the CTE does not promote policies that support a strategic sector for the national economy, such as transport, although it arguably can do so.